Development of a Mobile Application for Building Maintenance by Implementing Augmented Reality Technology - Awang Ismail Mohamed; Mohd Syafiq Syazwan Mustafa; Najeeha Mohd Apandi; Ahmad Rusyaidi Jumat; Maranatha Wijayaningtyas; Mohamad Fikri Mohamad Yunus (Journal of Advanced Industrial Technology and Application, 2025)
Building maintenance procedures are currently inefficient, which emphasizes the need for more creative and efficient solutions. In order to improve maintenance operations, the present study aims to develop a functional testing of a mobile application that combines Building Information Modelling (BIM) and Augmented Reality (AR). The development process was tested using Autodesk Revit to produce 3D models that included comprehensive equipment and building material specifications. Subsequently, the AR component of the application was developed using Unity Hub in conjunction with the Vuforia Software Development Kit (SDK). Alpha and Beta testing were deployed and tested in Android devices comprising two key phases. The application showed 100% operational stability with all features functioning as intended throughout alpha testing, which comprised internal evaluations to confirm functionality, stability, and usability. The System Usability Scale (SUS), which consists of 10 Likert-scale questions assessing user confidence, ease of interaction, and perceived usefulness, was used in beta testing to gather end-user input. Beta testing confirmed the system’s effectiveness, with an average SUS score of 72.5 and 90% of users reporting that the application is easy to learn and use. The study demonstrates that integrating AR with BIM in a mobile application fundamentally enhances building maintenance by streamlining processes. This study offers a solid foundation for further research and development and shows how combining AR and BIM might enhance conventional building maintenance.